Analysis of the Effects of Schema-Based and Mindful Parenting on Reducing Sleep Problems and Aggression in Children with Mild Autism Spectrum Disorder - Bakhtiari Shahri, Sedigheh; Rajaei, Alireza; Pourhydari , Sepideh (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to examine the effects of schema-based and mindful parenting training on reducing sleep problems and aggression in children with mild autism spectrum disorder (ASD). Methods: The research utilized a quasi-experimental design with pretest-posttest measurements, a control group, and a one-month follow-up. The study population consisted of 7- to 12-year-old children with mild ASD and their mothers from autism centers in Mashhad, Iran. Forty children (20 boys and 20 girls) and their mothers were selected using purposive sampling and randomly assigned to two intervention groups (schema-based and mindful parenting) and one control group. Both intervention groups received 12 weekly 90-minute training sessions, while the control group received no intervention. Data were collected using the Aggression Questionnaire and the Children’s Sleep Habits Questionnaire and analyzed with SPSS software using one-way ANOVA and covariance analysis (ANCOVA). Findings: Results showed that both schema-based and mindful parenting interventions significantly reduced sleep problems and aggression in children with mild ASD. The schema-based parenting group exhibited notable improvements in child-parent interactions and a reduction in maladaptive behaviors, while the mindful parenting group demonstrated enhanced maternal acceptance, reduced parenting stress, and improved emotional understanding of the child. Post-intervention comparisons indicated significant differences between experimental and control groups, with both interventions yielding positive impacts on sleep quality and aggressive behaviors. Conclusion: The findings suggest that schema-based and mindful parenting approaches can be effective in addressing sleep disturbances and reducing aggressive behaviors in children with mild ASD.